Faktor-Faktor yang Berhubungan dengan Kepatuhan Minum Obat pada Penderita Hipertensi Usia 45-65 Tahun - Innandah Annisa Lestari; Yunita Dyah Puspita Santik (Universitas Muhammadiyah Semarang, 2022)
Background: Hypertension is a disease that requires long-term therapy, so patient compliance is required in undergoing treatment to control blood pressure and reduce the risk of complications. In 2020, the Gunungpati Health Center experienced an increase of 9,956 cases and the rate of treatment adherence was 1314 patients. Objective: This study aims to determine the factors related to medication adherence in hypertensive patients aged 45-65 years in the Gunung Pati Public Health Center Work Area, Semarang City. Method: analytic observational design with a cross-sectional approach and a quantitative study was conducted by interview. Accidental sampling technique with a sample of 94 respondents. Meanwhile, data analysis was carried out univariate and bivariate using the chi-square test with the help of SPPS version 24.0. Result: There was a relationship between age (p = 0.000), gender (p = 0.025), employment status (p = 0.015), duration of hypertension (p = 0.014), hypertension level (p = 0.025), family support (p = 0.021), the role of health workers (p = 0.029) and motivation to seek treatment (p = 0.029) with adherence to taking hypertension medication aged 45-65 years. There is no relationship between the last education level (p=0.461), health insurance participation (p=0.459), and the affordability of access to health services (p=0.281). Conclusion: Increased progress for BPJS card holders to be more compliant in usage.